A Content Analysis of Reading Materials in Textbook Pathway to English For Tenth Graders Publsihed by Erlangga at Man Baturaja - Yulia, Henny; Agustiani, Merie (JR-ELT (Journal of Research in English Language Teaching), 2017)
This study is mainly to find out whether the English textbook used for the tenth grade students of Senior high School entitled Pathway to English for Senior HighSchool Grade X published by Erlangga is compatible or not with the indicators ofreading evaluation checklist suggested by Munir. This study was designed as a content analysis in the form of descriptive qualitative research. Reading materials that had been analyzed in this study were 16 text based on 2013 curriculum in tenth grades. Also, the genre that have been chosen to analyzed this study based on 2013 curriculum, its’ were descriptive text, recount text and narrative text. In textbook Pathway to English, there were 5 descriptive texts, 5 recount texts, and 6 narrative texts. The result showed that Pathway to English for Senior High SchoolGrade X have fulfilled the criteria of a good reading material suggested by Munirwith achieving the average fulfillment score of 71.66% with fulfillment score of 93.75% for aspect of content, 81.25% for aspect of skill, 20% for aspect of vocabulary and 91.66% for aspects of exercises and activities. It was then recommended that teachers need to modify the tasks and activities in textbook Pathway to English which did not fulfilled the criteria of poor reading material inthe area of vocabulary aspects.